Analisis Lahan Sektor Pertanian Di Kabupaten Kampar, Riau - Zustika, Rizki; Sasmita, Aryo; Isnaini, Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Agriculture is widely consists of several sectors including agriculture, plantation and livestock. The aim of research was to agricultural sector land analysis in Kampar District Province of Riau. The instruments used in this study are the Microsoft Excell Software 2010 and ArcMap Software 10.3 The data used is secondary data. The result is the agricultural land area consists of three commodities in Kampar district namely rice, crops and horticultural. The highest land area is derived from rice commodities covering an area of 9,159 ha.   Keywords: agriculture, agricultural sector land analysis,  Kampar District.